Numerical Tools for Composite Woven Fabric Preforming - Abel Cherouat; Houman Bourouchaki (Advances in Materials Science and Engineering)
An important step in the manufacturing processes of thin composite components is the layingup of the reinforcement onto the mould surface. The prediction of the angular distortion of the reinforcement during draping and the changes in fibre orientation are essential for the understanding of the manufacture process and the evaluation of the mechanical properties of the composite structures. This paper presents an optimization-based method for the simulation of the forming processes of woven fabric reinforced composites. Two different approaches are proposed for the simulation of the draping of woven fabric onto complex geometries: geometrical and mechanical approaches. The geometrical approach is based on a fishnet model. It is well adapted to predimensioning fabrics and to give a suitable quantification of the resulting flat patterns. The mechanical approach is based on a mesostructural model. It allows us to take into account the mechanical properties of fibres and resin and the various dominating mode of deformation of woven fabrics during the forming process. Some numerical simulations of the forming process are proposed and compared with the experimental results in order to demonstrate the efficiency of our approaches.